Commercial Agriculture, the Slave Trade and Slavery in Atlantic Africa - Robin Law, Suzanne Schwarz, and Silke Strickrod (James Currey, 2013)
This volume presents a selection of papers from a conference held at the German Historical Institute London (GHIL), in September 2010, on the topic of ‘Commercial Agriculture in Africa as an Alternative to the SlaveTrade’.This Introduction begins by situating this topic in its context within the history and historiography of western Africa.The idea of promoting the export of agricultural produce fromAfrica first became central to European thought in the context of the campaign to end the trans-Atlantic slave trade from the late eighteenth century onwards, with actual projects on the ground inWest Africa beginning with Danish attempts to establish plantations on the Gold Coast (modern Ghana) from 1788, followed by the British2 colony of Sierra Leone, after it was taken over by the Sierra Leone Company in 1791.3 After the legal abolition of the slave trade in the early nineteenth century, proposed commercial alternatives to it became known in contradistinction as ‘legitimate’ (or ‘legal’ or ‘lawful’) commerce (or trade).4 Strictly, the term ‘legitimate commerce’ designated trade in anything other than slaves, including non-agricultural commodities such as gold and ivory, but in practice interest was mainly concentrated on the promotion of commercial agriculture. Rationales for this interest in agricultural exports were various. Most immediately, it was thought thatWest Africa could take the place of the Americas as a supplier of sugar and other tropical products to Europe, with African labour retained and employed locally rather than being transported across the Atlantic, thereby dispensing with the need for the trans-Atlantic slave trade: this was, for example, the thinking behind the Danish project of 1788. Beyond this, there was the desire to develop a form of trade which it was hoped would be more beneficial to Africa itself, given that the impact of the slave trade was commonly assumed to have been negative and destructive. WilliamWilberforce, for example, proposing abolition of the slave trade to the British Parliament in 1789, argued that the development of alternative forms of trade to replace it would represent a means of compensating for the harm which Europeans, through the slave trade, had done to Africa: ‘Let us make reparation to Africa, as far as we can, by establishing a trade upon true commercial principles.